From Student Engagement to Student Agency: Conceptual Considerations of European Policies on Student-Centered Learning in Higher Education. Issue 1 (March 2017) - Klemenčič, Manja
Abstract Student-centered learning (SCL) has entered center stage on the European higher education (HE) policy agenda after the Yerevan Ministerial Summit of the European Higher Education Area (EHEA) in May 2015. It has become the key principle underlying the intended reforms toward enhancing the quality of teaching and learning in European HE. Despite the universal appeal, SCL remains poorly defined in policy documents and this ambiguity potentially jeopardizes its implementation. The article addresses the different instances and evocations of the SCL approach in EHEA policies. Furthermore, it seeks to clarify the conceptual foundations of SCL. Two propositions are put forward. First, SCL should be understood as a 'meta-concept'. Such an understanding serves as a corrective to the eclectic use of SCL in association with a broad variety of policy issues. Second, the article questions the suitability of student engagement as a conceptual foundation of SCL. The main argument is that student engagement conceptually fails to sufficiently address student autonomy, self-regulation and choice, all of which have been highlighted by the literature as essential elements of SCL. The root concern of SCL is not propensity to different types of student action as implied in student engagement, but rather student agency as students' capabilities to intervene in and influence their learning environments and learning pathways.